2006
DOI: 10.1017/s1355617706060474
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen and performance in recognition memory for olfactory and visual stimuli in females diagnosed with Alzheimer's disease

Abstract: Patients with Alzheimer's disease (AD) exhibit a deficit in episodic recognition memory for odors. It is hypothesized that the higher rate of AD in women may be due to estrogen-deprivation in postmenopausal women. Research suggests that estrogen may help to minimize cognitive decline in AD as well as postmenopausal olfactory loss. The current study examined the effects of estrogen replacement therapy (ERT) on performance of a recognition memory task for olfactory and visual stimuli in women AD patients. Partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Our finding of an influence of HRT on an odor memory/discrimination task appears to be in accord with the study of Sundermann et al (2006) in which HRT enhanced performance on an odor recognition memory test in 24 postmenopausal women. However, their subjects had AD, unlike ours, and we controlled for potential confounding influences of IQ in our analyses.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our finding of an influence of HRT on an odor memory/discrimination task appears to be in accord with the study of Sundermann et al (2006) in which HRT enhanced performance on an odor recognition memory test in 24 postmenopausal women. However, their subjects had AD, unlike ours, and we controlled for potential confounding influences of IQ in our analyses.…”
Section: Discussionsupporting
confidence: 90%
“…Nonetheless, some later studies employing larger samples supported these early observations. For example, Sundermann et al (2006) reported that ERT improved performance in 24 postmenopausal women with AD on an odor recognition memory task. Such improvement was noted in a later study by these same authors for a threshold test in 16 older non-demented women, but this effect was evident only in women positive for the APOE-ε4 allele, a risk factor for AD (Sundermann et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It has been postulated that estrogen deficiency, following menopause, may contribute to the etiology of the disease. In a 12 case-control and cohort studies conducted in the 1990s, it was suggested that estrogen therapy could delay the onset or contribute to the prevention and/or significantly attenuation of AD (Sundermann et al, 2006 ), but this question is still under discussion (Asthana et al, 1999 ; Henderson et al, 2000 ; Mulnard et al, 2000 ; Henderson, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike menstruation or conception, menopause has not been a major topic of discussion among the public. Very little information has been circulated to the public to increase knowledge on the subject (Sundermann et al, 2006;Fakhsheena Anjum, 2013;Liu, 2007).…”
Section: Basic Subject Characteristicsmentioning
confidence: 99%
“…Unfortunately, FSH levels are what most doctors use to diagnose menopause. Estrogen is made from a variety of sources (Sherwin, 2005;Sundermann et al, 2006). The ovary is only one of many sources.…”
Section: Introductionmentioning
confidence: 99%